PENGARUH PEMANFAATAN LAHAN TERHADAP EKOSISTEM PESISIR DI KAWASAN TELUK AMBON - Yulia Asyiawati (Jurnal Perencanaan Wilayah dan Kota, 2010)
This study aims (1) to analyzing the shift in utilization patterns compared with the carrying capacity and land suitability; (2) to analyze the status of coastal ecosystems. The method of analysis used in this study is the analysis of Geographic Information System (GIS).The results showed that there was a shift utilization, namely: to change the function of protected areas into mixed areas and dryland farming for 83.12%, coastal border that changes the function into the airport area, mixed area, settlements, dry land farming for 96.02%, dry land agriculture which transformed the function into neighborhoods, the area is a mixture of 8.70%. This resulted in the status of coral reef ecosystems, including criteria for medium-well with percentage coral cover ranged from 36.63 to 75.62%, the status of mangrove ecosystems including the category tree density was 780 to 1420 trees / ha, and the status of seagrass ecosystems, including categories less rich with the percentage cover ranged from 33.13% to 44.39%.